Diseño de un plan de mejoramiento para Distribuidora T.A.T Surtimax de la ciudad de Armenia. (2013)
TAT is a distributor Surtimax distribution consumer products located at Cra 16 - # 14-14 city center Armenia The company is divided into 3 areas of work , administrative, financial and distribution , have the necessary equipment to operate and all activities Subsequently , an analysis of the current situation of the company under study , ie , its principal activities, covering the market , its geographic, demographic and profile description of the client is performed After establishing the current situation we proceed to the formulation of the proposed plan taking as part of the sales force study The analysis through the SWOT technique created diagnostic guidelines for the design of strategies for quality and credibility , which are fundamental pillars that will stimulate demand for consumer products . As well as the tactics that were used for the achievement of objectives , the implementation of elements of strategic planning and incentives aimed at promoting sales force to improve employee productivity and hence the performance of them reflected in the volumes every sales advisor Only the implementation of policies and strategies that enable business The distributor keeps solid in a market where there is always a waiting customer needs and expectations are met. This work is expected to Distribuidora TA T SURTIM , AX increase sales and have higher profits while increasing the market and attract new customers and sales force is motivated to achieve their career goals and professional giving the company growth in sales and reach targets implementing these strategies described in this work on behalf of this marketer will be reflected in the sales volume.